Beliefs and attitudes of Canarian speakers towards Andean Spanish - Samper Hernández, Marta (2025)
Despite the existing links between Canarian Spanish and the American varieties, there is so far no study that addresses the perceptions of Canarian speakers towards the Andean modality. The main objective of this work, carried out within the framework of the precaves xxi project (Project for the Study of Beliefs and Attitudes Towards Spanish Varieties in the 21st Century), is to analyze the beliefs and attitudes towards Andean Spanish of 108 Canary Islanders with no specialized linguistic training. For this purpose, the methodology created by Cestero and Paredes in 2013 is used, which consists of listening to the voices of educated speakers of the different varieties of Spanish, together with a series of direct and indirect questions about them. The analysis is carried out both in a general way and according to the social variables such as gender, age and level of studies. The results obtained from the evaluation of the Colombian speech samples reveal a conception of Andean Spanish as a considerably prestigious variety from a linguistic point of view and in relation to its speakers, but which is in turn linked to an area and a culture somewhat more distant from the models of social prestige.